Consultant staffing in UK congenital cardiac services: a 10-year survey of leavers and joiners. Issue 2 (8th July 2021) - Crossland, David Steven; Ferguson, Richard; Magee, Alan; Jenkins, Petra; Bulock, Frances A; Parry, Andrew; Babu-Narayan, Sonya V; Carroll, Aisling; Daubeney, Piers EF; Simpson, John
Abstract : Objectives: To report the numbers of consultant congenital cardiac surgeons and cardiologists who have joined and left UK practice over the last 10 years and explore the reasons for leaving. Methods: Retrospective observational questionnaire study completed between 11 June 2019 and 1 July 2020 by UK level 1 congenital cardiac centres of 10-year consultant staff movement and reasons suggested for leaving UK practice. Results: At survey completion there were 218 (202 whole time equivalent (WTE)) consultant cardiologists and surgeons working within level 1 centres made up of 39 (38 WTE) surgeons, 137 (128.5 WTE) paediatric cardiologists, 42 (35.5 WTE) adult congenital heart disease (ACHD) cardiologists. 161 (74%) consultants joined in the last 10 years of whom 103 (64%) were UK trained. There were 91 leavers giving a staff turnover rate 42% (surgeons 56%, paediatric cardiologists 42%, ACHD cardiologists 29%). Of those, leaving 43% moved to work abroad (surgeons 55%, paediatric cardiologists 40%, ACHD cardiologists 67%). Among the 65 reported reasons for leaving 16 were financial, 9 for work life balance, 6 to working conditions within the National Health Service (NHS) and 12 related to the profession in the UK including six specifically highlighting the national review process. Conclusions: There has been a high turnover rate of consultant staff within UK congenital cardiac services over the last 10 years with almost half of those leaving moving to work overseas. Financial reasons and pressures relating to working in the NHS or the specialty in the UK were commonly reported themes for leaving. This has major implications for future planning and staff retention within this specialised service.